PENGARUH PELATIHAN MEDIA PEMBELAJARAN CANVA TERHADAP KOMPETENSI GURU DI SMA NEGERI 2 SELAYAR - A. Bakri S; Abd. Haling; Merrisa Monoarfa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to describe the implementation of Canva learning media training at SMA Negeri 2 Selayar, to describe teacher competency in Canva learning media training at SMA Negeri 2 Selayar and to describe the influence of Canva learning media training on teacher competency at SMA Negeri 2 Selayar. The approach used is quantitative research, while the type of research used in this research is pre-experimental. The subjects in this research were 25 teachers at SMA Negeri 2 Selayar. Meanwhile, the research object that will be studied here is Canva media training. Data collection using observation, tests and documentation. Data analysis uses descriptive analysis and inferential statistical analysis. The results of this research show that the description of the implementation of Canva media training carried out at SMA Negeri 2 Selayar includes both theoretical and practical material with a recapitulation of the results of the activity analysis of the training participants with the percentage of achievement levels being in the very effective category. The competency description shows an increase in teacher understanding after attending the training. The implementation of Canva learning media training showed very effective results based on the analysis of the training participants. The results of data analysis show that there are significant differences. This also answers hypothesis H1, namely that there is an influence of Canva Learning media training on teacher competency at SMA Negeri 2 Selayar.